Pendidikan Lingkungan: Plastic Pollution Awareness di Desa Jatireja, Cikarang, Jawa Barat - Filson M Sidjabat; Yunita Ismail; Evi Rismauli (President University, 2019)
Waste problems in Indonesia has reached a critical point that is contaminating many aspects in community. Poor waste management in land have an impact in water pollutions, rivers, and toward the ocean. This rivers and oceans pollution are become the spotlights for the world and the government. As a part of education community in West Java, President University has an important role to educati and find solutions relate with this issues, one of them is to implement Thidharma in the form of social empowerment in Jatireja Village. This environmental education activities was sharing knowledge about plastic waste treatment and management that can be conducted in household scale, and to encourage behavioral change and awareness among communities. Creative product of eco-brick was also implemented tas a part of waste utilization to make valueable product. Environmental education are needed to improve community awareness on plastic waste in Indonesia, especially in West Java.